Ambiguity Between The Placement Of Zakat Collecting Objects And The Tax Payable (Literature Study) - Faidul Adziem; Mira Mira (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the clarity of the ambiguity of the placement of objects to collect zakat and tax payable through the concept of zakat as a direct tax deduction, the opinion of scholars about zakat and taxes, the opinion of previous researchers about zakat as a direct tax deduction, the opinion of the Qur'an, hadith and regulations. the law on zakat and taxes, as well as the difference between zakat as a deduction from taxable income and zakat as a direct tax deduction. . This research was conducted by literature study method, namely the researcher used data collection techniques in the form of library research and literature review. The results of this study that zakat as a direct deduction of taxes or taxes payable (tax credit), is an effective way compared to zakat as a deduction of taxable income because there will be an increase in the tax ratio, namely the number of taxpayers will be more and more. Muslim taxpayers will be more eager to pay zakat and taxes, because there are no more double payments.